Potentials of Telemedicine for Green Health Care - Audebert, Heinrich; Meyer, Thomas; Klostermann, Fabian (Frontiers in Neurology, 2010)
Neurological facilities are traditionally centred in academic hospitals and often far away from the patients’ living area. Both, the transfer of patients to remote hospitals and inpatient treatment are associated with high energy consumption. Numbers of patients with neurological diseases are expected to increase along with the demographical changes and the environmental impact of neurological treatment should become a target for health policy, therefore. Positive effects have been demonstrated for the use of telemedicine by improving inpatient treatment in local community hospitals or avoiding hospital admissions via monitoring of complex diseases in outpatient settings. We discuss the potentials of telemedicine in the field of in- and outpatient neurological care as well as the need for more scientific evaluation on environmental impacts.